Consensus on Treatment of Acne Scars in China (2021)# - Laser Cosmetology Group, Medical Aesthetics and Cosmetology Branch of Chinese Medical Association; Cosmetic Laser Group, Chinese Society of Dermatology; Laser Group, Cosmetic and Plastic Surgeon Branch of Chinese Medical Doctor Association; Sen Yang; Zhong Lu; Tong Lin; Guo-Yu Zhou; Min Yao; Yi Liu; Rong-Ya Yang; Zhi-Fei Liu; Yuan-Hong Li; Dong-Ni Li; Xiao-Dong Chen; et al. (Wolters Kluwer Health, 2022)
Acne scars are caused by inflammatory reactions, infections, and improper handling of acne lesions. Such scars have a high incidence and are difficult to treat. There are many methods currently used to treat acne scars, including medications, photoelectric technology, surgery, filling, chemical peeling, traditional Chinese medicine, biotherapy, and microneedle therapy, and many new methods are constantly emerging. However, there are still many issues, such as the lack of high-quality clinical studies, non-uniform treatment methods, and unsatisfactory therapeutic effects. The selection of appropriate methods for the comprehensive treatment of different types of acne scars at different stages in clinical practice remains challenging and is a research topic of great interest. From the perspective of evidence-based medicine, this consensus aims to provide a reference for the treatment of acne scars in clinical practice.